2017
DOI: 10.4149/bll_2016_133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anatomical variation in the nasal cavity and paranasal sinuses of patients with cleft lip and palate using cone beam computed tomography

Abstract: OBJECTIVE: The aim of this study was to evaluate the frequency of anatomical variation in nasal cavity and paranasal sinuses by comparing a unilateral cleft lip and palate (UCLP) group with a non-syndromic control group using cone beam computed tomography (CBCT). SUBJECTS AND METHODS: This study included 24 UCLP patients in the UCLP group and 24 non-syndromic patients in the control group. Coronal CBCT images were taken in all patients and were evaluated for anatomical variation. The measurements obtained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
4
17
0
1
Order By: Relevance
“…According to the findings in the present study, incidence of NSD was significantly higher in patients with cleft than the control group. Similarly, previous investigations demonstrated that the UCLP group obtained a higher incidence of anterior NSD compared to the unaffected controls, which is in line with the results of our study (Kuijpers et al, 2014; Dedeoglu et al, 2016; Santos et al, 2020). The increase in the size of nasal wings can be seen in patients with UCLP.…”
Section: Discussionsupporting
confidence: 93%
“…According to the findings in the present study, incidence of NSD was significantly higher in patients with cleft than the control group. Similarly, previous investigations demonstrated that the UCLP group obtained a higher incidence of anterior NSD compared to the unaffected controls, which is in line with the results of our study (Kuijpers et al, 2014; Dedeoglu et al, 2016; Santos et al, 2020). The increase in the size of nasal wings can be seen in patients with UCLP.…”
Section: Discussionsupporting
confidence: 93%
“…Although these variable rates seen in the literature may be caused by the differences in imaging techniques used in the study, the evaluated section thickness is essential for minor variations. In a previous study, the incidence of Agger nasi cells was found to be 100% in patients with CLP and the control group (Dedeoglu et al, 2016). In our study, the frequency of Agger nasi, 97% in the CLP group and 99% in the control group, are consistent with the literature.…”
Section: Variation Of Ethmoidal Cellssupporting
confidence: 92%
“…The presence of maxillary sinus pathologies and septa require extra carefulness in dental implant procedures [10]. It is known that some anatomical variations of paranasal sinus can cause a tendency to infections while others can cause surgical complications [2,3]. It was reported that variations of the maxillary sinus such as accessory maxillary ostium and Haller cell could lead to sinusitis [2,22].…”
Section: Introductionmentioning
confidence: 99%